Pengaruh Persepsi Siswa Tentang Kompetensi Pedagogik Guru Dan Disiplin Belajar Siswa Terhadap Prestasi Belajar Siswa Jurusan Manajemen Perkantoran Pada Mata Pelajaran Kearsipan Di SMK Negeri 6 Surakarta - Titin Prasetyani; Wiedy Murtini; Winarno Winarno (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
The purpose of this study was to determine the influence of (1) student’s perceptions of teacher pedagogic competence on the learning achievement of students majoring in Office Management in archival subjects at SMK Negeri 6 Surakarta, (2) discipline learning on the learning achievement of students majoring in Office Management in archival subjects at SMK Negeri 6 Surakarta (3) student’s perceptions of teacher pedagogic competence and learning discipline together on the learning achievement of students majoring in Office Management in archival subjects at SMK Negeri 6 Surakarta. This type of research is quantitative research. Data collection is carried out by the distribution of questionnaires. The results of this study show that 1) There is a significant negative influence between student's perceptions of teacher pedagogic competence on student learning achievement in archival subjects of students majoring in office management at SMK Negeri 6 Surakarta in the 2022/2023 school year (tcount (-2,515) < ttable (1,989)) ; 2) There is a positive and significant influence between disciplines learning on student achievement in archival subjects of students majoring in office management at SMK Negeri 6 Surakarta in the 2022/2023 academic year (tcount (2,169) > ttable (1,989)); 3) There is a simultaneous positive and significant influence between 2 – student's perceptions of teacher pedagogic competence and discipline learning on learning achievement (Fhitung (3.679) > Ftabel (3.108))